- Perancangan Visual Identity Bolu Salak Kenanga: Perancangan Visual Identity Bolu Salak Kenanga - erwanti (IAM Indonesia, 2023)
Culinary developments in Padangsidimpuan are increasing rapidly over time. Almost every region in Indonesia has its own special culinary. Moreover, Padangsidimpuan has various types of culinary specialties. The food industry continues to grow following the trend. Various types of food appear along with the increasing popularity of the culinary world. The city is known as the City of Salak because the city is surrounded by hills and mountains, which are the area for Salak fruit plantations. In the Padangsidimpuan City area, there are several well-known cake businesses such as the Kenanga Salak Cake. As part of the rebranding process, Bolu Salak Kenanga must also build a brand image as a strong image in society. The purpose of this design is to design the visual identity of Bolu Salak Kenanga. The data analysis method used is the SWOT (Strength, Weakness, Opportunity, Threat) method. The theoretical approach used is design principles, design elements, design elements and the notion of identity. The concept in this design is a combination of character and cultural values ??possessed by salak ylang cake. The design process produces the main media in the form of a logo which becomes the visual identity of Bolu Salak Kenanga and several other supporting media such as packaging, box design, tape, paper bags, posters, x-banners, t-shirts, business cards, stickers and neon boxes. Keyword: logo, visual identity, bolu salak kenanga